SPINAL INTRADURAL EXTRAMEDULLARY TUMORS AND SIMILAR PATHOLOGIES: A SINGLE CENTER STUDY - Altınel, Faruk; Pekcan, Yonca Özvardar; Sivrikoz, Oya Nermin (PERDOSSI (Perhimpunan Dokter Spesialis Saraf Indonesia Cabang Malang) - Indonesian Neurological Association Branch of Malang cooperated with Neurology Residency Program, Faculty of Medicine Brawijaya University, Malang, Indonesia, 2024)
Background: We wanted to analyze the neurological symptoms and prognosis of five spinal IDEM (intradural extramedullary) tumors cases diagnosed, and to emphasize that a spinal cord tumor can be found incidentally in evoluation of the proximal regions of the vertebral column in patients who were mistakenly operated for lumbar disc herniation on lumbar MRI, but whosesymptoms did not resolve. Objective: To emphasize the need for examinations such as MRI along the vertebral columna in patients with different spinal pathologies and whose symptoms and clinical signs do not improve. Methods: Patients with spinal IDEM tumors treated with surgical excision and followed for more than 2 years were retrospectively analyzed. Issessed pain with the visual analo scale (VAS), and neurological function with the Nurrick grade.Preoperative complaint time,location of tumor in sagital and axial sections in MRI and pathological diagnosis were investigated. Results: The pathological diagnosis in our study was meningioma in two cases,dural arteriovenous fistula in one case,teratoma in one case ,and myxopapilary epandimoma in one case.İn one case,disc herniation surgery was performed in another hospital due to misdiagnosis, but because the patient’s complaints were resistant. In examination, an IDEM tumor at T11 level was detected, and he was operated. In all cases the VAS score (mean) was reduced from 7.8 to 0.4 as well as the Nurrick grade (mean) was from 2.0 to 0.6. In the dAVF case, spasticity in the lower extremities, bladder and bowel disfunction continued. Conclusion: In cases with severe neurological deficits, MRI scanning of the proximal parts of the vertebral column will help in the differential diagnosis of the lesion occupying the intraspinal space.